Evaluation of Growth and Health Performance of Juvenile Tilapia Oreochromis sp. Fed with Various Supplementation of Heat-Killed Lactobacillus plantarum - Julie Ekasari; Vini Nur Mirza; Ichsan Achmad Fauzi; Kyohei Hashimoto; Muhammad Agus Suprayudi (Aquaculture Nutrition)
Thus, this research was conducted to evaluate the supplementation of heat-killed Lactobacillus plantarum at higher dosages and investigate the effect of heat-killed L. plantarum supplementation on the challenges of Streptococcus agalactiae. A feeding trial was conducted for 90 (initial average body weight of 12.52–12.69 g) days, while a disease challenge was conducted for 17 days. Dietary treatments were formulated to have a ranging level of heat-killed L. plantarum L-137: (1) control treatment without heat-killed L. plantarum, (2) diet containing 10 mg/kg heat-killed L. plantarum L-137 preparation (LP20, which contains 20% heat-killed L. plantarum L-137), (3) diet containing 20 mg/kg LP20, (4) diet containing 100 mg/kg LP20, and (5) diet containing 250 mg/kg LP20. All the diets were formulated to have equal values of protein and energy. Dietary supplementation of heat-killed L. plantarum L-137 improved tilapia growth performance and higher robustness against S. agalactiae infection. Therefore, a 10–20 mg/kg LP20 feed supplementation level is recommended to support the tilapia growth. In addition, an LP20 dietary supplementation level of 250 mg/kg feed is recommended for higher protection against S. agalactiae.